Flow alteration and thermal pollution depress modelled growth rates of an iconic riverine fish, the Murray cod Maccullochella peelii. Issue 3 (23rd October 2017) - Whiterod, Nick S.; Meredith, Shaun N.; Humphries, Paul; Sherman, Bradford S.; Koehn, John D.; Watts, Robyn J.; Ingram, Brett A.; Ryan, Tom
Abstract: The serial discontinuity concept (SDC) proposes that hypolimnetic‐releasing impoundments cause major disruptions to the naturally occurring physical, chemical and biological gradients of rivers but that this impact diminishes with distance downstream. Such a gradient in discharge, flow velocity and temperature regime occurs below a large hypolimnetic‐releasing impoundment, the Hume Dam, on the River Murray in south‐eastern Australia. To examine the effects of this disturbance gradient on a warm‐water large‐bodied freshwater fish, the Murray cod ( Maccullochella peelii ), a bioenergetics model was developed and calibrated to explore energy expended under differing water velocities and temperature regimes. Model simulations predicted negative growth of juveniles directly downstream of the impoundment, due largely to the energetic costs associated with active and, to a lesser extent, standard metabolism outweighing the achievable energetic gains through food consumption. As flow velocity and temperature regimes became more favourable downstream, so did the simulated growth of the species. It was not until +239 km downstream of the impoundment that the model predicted that flow velocity and temperature regimes were suitable for greater weight gains. The modelled growth responses of juvenile Murray cod are consistent with the predictions of the SDC, emphasising that changes in the bioenergetics of individuals are likely to be reflected in reduced growth rates under the changed flow velocity and temperature regimes imposed by disturbance gradients. This research represents a valuable step in the biological understanding of Murray cod within variable riverine environments and emphasises the urgency required to mitigate impacts associated with hypolimnetic impoundments.